Open and distance learning (ODL): Preference and perception of students towards live lecture and pre-recorded video lecture / Syah Runniza Ahmad Bakri ... [et.al.]. - Ahmad Bakri, Syah Runniza; Salleh, Juliza; Hamdan, Anniza; Bujang, Noriham; Julaihi, Nor Hazizah; Che Md Nor, Rumaizah; Zainuddin, Puteri Faida Alya; Ismail, Nor Huwaina (Universiti Teknologi MARA Cawangan Sarawak, 2022)
The outbreak of COVID-19 has forced many countries to close their educational institutions temporarily. It has transformed the educational system into adopting online-based learning. There are many challenges faced by students in online-based learning, such as slow internet connection and inconvenient learning environments. This has led to various onlinebased learning methods to address students' needs. This paper investigates the most preferred method among students and their perceptions. An improvement in the learning level of students was investigated based on their perceptions. An online self administered questionnaire was disseminated to students from three campuses of UiTM Sarawak (Samarahan, Samarahan 2, and Mukah). Data obtained from a sample of 1199 students was analyzed using descriptive statistics to measure students' perception of the method that they preferred. The resultsshow that the mixed delivery method was the most preferred method among students for online learning, which accounted for 63.9%.